The Ḥanbalī school of law and Ibn Taymiyyah : conflict or conciliation - Al-Matroudi, Abdul Hakim I. (London ; New York : Routledge, 2006)
In this book, the life of the 14th century jurist Ibn Taymiyyah and his position within Hanbali tradition is analysed. It is an original piece of research, taking into consideration the issues involved in madhhab affilation and Hanbali fiqh.
BOOK COVER; HALF-TITLE; SERIES-TITLE; TITLE; COPYRIGHT; CONTENTS; TABLES; PREFACE; ACKNOWLEDGEMENTS; NOTE ON TRANSLITERATION; INTRODUCTION; 1. IBN HANBAL AND IBN TAYMIYYAH; 2. A COMPARISON OF THE BASIC PRINCIPLES OF ISLAMIC LAW ACCORDING TO IBN HANBAL AND IBN TAYMIYYAH; 3. RE-LAYING THE FOUNDATIONS: Ibn Taymiyyah and Hanbali usul; 4. RECONSTRUCTION: Ibn Taymiyyah and Hanbali jurisprudence; 5. THE LEGACY: The influence of Ibn Taymiyyah on Hanbali jurists; 6. A CASE OF CONFLICT?: The intended triple divorce revisited; CONCLUSIONS; NOTES; BIBLIOGRAPHY; INDEX.
Includes bibliographical references (pages 192-274) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Ibn Taymīyah, Aḥmad ibn ʻAbd al-Ḥalīm, -- 1263-1328.; Ibn Taymīyah, Aḥmad ibn ʻAbd al-Ḥalīm, -- 1263-1328; Hanbalites; Ḥanbalites.; RELIGION -- Islam -- Law; Hanbalites